Herbal Extract-Infused Biopolymers as Sustainable Film Formers in Skin and Hair Care Products - Priyanshu Upadhyay (Recent Trends in Cosmetics, 2024)
Herbal extracts are becoming increasingly popular in cosmetic formulations. Due to increasing customer demand for natural, sustainable products. This review explores the potential of herbal extract-infused biopolymers as innovative film-formers in skin and hair care applications. Biopolymers, derived from natural sources, offer excellent biocompatibility, biodegradability, and functionality, making them suitable for enhancing the performance of cosmetic products. This article examines various herbal extracts that can be synergistically combined with biopolymers to enhance their properties, focusing on aspects such as moisturizing effects, anti-aging benefits, and hair health improvements. Additionally, the review discusses the formulation strategies, challenges, and future perspectives of utilizing herbal extract-infused biopolymers in the cosmetic industry. The findings highlight the importance of sustainability in cosmetic formulation, emphasizing the need for continued research to develop effective, eco-friendly products that meet consumer demands for both efficacy and environmental responsibility. The future of herbal extract-infused biopolymers is promising, with trends pointing toward personalized skincare, innovative delivery systems, and sustainable practices. Continued research into the efficacy and safety of these formulations will drive their acceptance and success in the market.
Keywords: Anti-aging; Biopolymers; Cosmetic formulation; Eco-friendly products; Film-formers; Hair care; Herbal extracts; Moisturizing; Natural ingredients; Skin care; Sustainable cosmetics; biodegradability